Statistical Analysis of the Characteristic Features of Standard Image for Racial and Ethnic Identity of a Person - Mahmudova, Shafagat Jabrail (European Journal of Applied Sciences, 2015)
The paper provides statistical analysis of the characteristic features used to determine racial and ethnic identity of a person basing on the images. Standard characteristic features of the persons of each ethnic group have been set accordingly. Characteristic features of random image have been compared with the characteristic features of standard image to determine belonging of a person to this or that racial and ethnic group. Comparing the characteristic features of the random image with the characteristic features of the standard image of each ethnic group, it is important to define the reliability of the interdependence between them. Note that, characteristic features of standard image were determined basing on the characteristic features of a real human face belonging to each ethnic group. The dependence was defined among the characteristic features of racial and ethnic standards set up according to the images with the characteristic features of a human face. A Fischer criterion was used to determine the dependence.